Synthesis of 1,3-dichloropropanol from glycerol using muriatic acid as chlorinating agent - Rahman, Herliati; Yunus, Robiah; Rashid, Umer; Zainal Abidin, Zurina; Ahamad, Intan Salwani (Chemic Publishing Company, 2014)
Today, one of the problems associated with biodiesel production is the availability of high amount of glycerol byproduct. Among the various possibilities, technology to convert glycerol to dichloropropanol has diverted our attention. Dichloropropanol an important raw material for epichlorohydrin production was successfully synthesized via hydrochlorination reaction of glycerol with aqueous hydrogen chloride to produce 1,3-dichloropropanol. Experimental study was carried out under temperatures ranged; 80 to 120 °C, reactant molar ratio; 1:16 to 1:32 and various carboxylic acid catalysts. The optimal reaction conditions were: temperature, 110 °C; reactant molar ratio glycerol to HCl, 1:24; catalyst, malonic acid; and time duration, 3 h.